The Knowledge, Attitudes, and Practices of Healthy Eating Questionnaire: a pilot validation study in Chinese families - Liu, Kiki S. N.; Chen, Julie Y.; Sun, Kai-Sing; Tsang, Joyce P. Y.; Ip, Patrick; Wong, Carlos K. H.; Lam, Cindy L. K. (Frontiers in Public Health, 2024)
Introduction: Identifying the knowledge, attitudes and practices (KAP) gaps of healthy eating can inform the design of effective interventions. This study aimed to test the validity and psychometric properties of a KAP of Healthy Eating Questionnaire (KAP-HEQ) that was tailored to the Chinese culture.The dimensions and potential items of each KAP scale were identified from published KAP and health literacy questionnaires, which were supplemented by the findings of a previous qualitative healthy eating study. Content validity of the KAP-HEQ was evaluated by 8 experts and 8 Chinese parent-adolescent dyads in Hong Kong, by means of content validity ratio (CVR), content validity index (CVI) and qualitative feedback. The feasibility, construct validity, reliability and sensitivity of the KAP-HEQ were evaluated in this pilot study among 60 adolescent-parent dyads (120 persons) through an online survey. The first 30 dyads who completed the KAP-HEQ were invited to repeat the KAP-HEQ two weeks later to assess the test-retest reliability. The final 44-item KAP-HEQ could be completed in 10 to 15 minutes by both adolescents and their adult parents. The CVR ranged from -0.38 to 1, and the CVI ranged from 0.56 to 1. Over 80% of the items achieved convergent validity (a significantly positive correlation with its hypothesized scale) and discriminant validity (a higher correlation with its hypothesized scale than with the other two scales). The Cronbach's alpha on internal consistency of the Overall, Attitude and Practice scales were > 0.7 but that of Knowledge scale was 0.54. The ICC on test-retest reliability of the Overall and individual scales were all > 0.75 except that of Knowledge scale (ICC=0.58). The significant differences in KAP scale scores with small to large effect sizes were found between known-groups as hypothesized, except the Attitude score between groups by household income, which supported the sensitivity of KAP-HEQ.The KAP-HEQ has shown good validity, reliability and sensitivity among Chinese adolescents and adults, which can be applied to evaluate KAP status and gaps to inform the design and assess the effectiveness of healthy eating interventions.